Temperature trends in the Syrian Badia region during the period 1970-2020 - Fallah, Riad Mahmoud Qara; Khaddam, Rasha Youssef (Journal of natural sciences, life and applied sciences, 2022)
The research aimed to analyze the value of the slope of the general trend line of average temperatures to determine the amount of annual and seasonal temperature change in the Syrian Badia region during 51 years, and to compare the temperature change during the period 1970-2000 with the period 2001-2020 by using the deductive and inductive approaches, statistical methods and information systems Geographical 10.2Arc GIS. The results showed a statistically significant increase in the general trend line of the average annual and seasonal temperatures in all stations during the period 1970-2020, and the increases ranged between 2.5 °C in most stations and 3.2 °C in the summer. The temperature increased in the period 2001-2020 compared to the period 1970-2000 by 1.3 °C in most stations, in a statistically significant way. The maps of the spatial distribution of temperatures show an increase in annual temperatures over the area of the region in the eastern and northeastern regions, and the most prominent change in Al-Tanf station is by 2.6°C.